2020
DOI: 10.1371/journal.pone.0237140
|View full text |Cite
|
Sign up to set email alerts
|

The motivation for citizens’ involvement in life sciences research is predicted by age and gender

Abstract: Open Science is an umbrella term encompassing multiple concepts as open access to publications, open data, open education and citizen science that aim to make science more open and transparent. Citizen science, an important facet of Open Science, actively involves nonscientists in the research process, and can potentially be beneficial for multiple actors, such as scientists, citizens, policymakers and society in general. However, the reasons that motivate different segments of the public to participate in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 49 publications
2
27
2
Order By: Relevance
“…The finding that gender was not related to the different motivational factor items also differs from earlier research, which has found that women are more driven by intrinsic motives for involvement in research than men [ 29 ]. Previous studies have also highlighted that informal caring affects women more negatively than it does men [ 15 , 51 ], which may explain why women were more motivated by family reasons.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The finding that gender was not related to the different motivational factor items also differs from earlier research, which has found that women are more driven by intrinsic motives for involvement in research than men [ 29 ]. Previous studies have also highlighted that informal caring affects women more negatively than it does men [ 15 , 51 ], which may explain why women were more motivated by family reasons.…”
Section: Discussioncontrasting
confidence: 94%
“…Our results showed that certain characteristics were related to different motivations for active involvement in research. Older age seemed to be connected with an overall lower motivation, a result inconsistent with earlier research, which showed that intrinsic reasons for involvement increased throughout a person’s lifetime [ 29 ]. Again, this could possibly be explained by the complexity of informal caring, where earlier research has shown that the perceived caring burden develops and in many cases increases over time [ 23 , 50 ].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The gender composition of our sample is, however, largely reflective of the wider UK nursing, midwifery, social care, and social work workforce [ 57 , 58 , 59 ] and also of other countries’ health and social care workforce, which is mainly female, with lower pay and working conditions [ 60 ]. Another or accompanying explanation for the gender composition of respondents is also possible; females may have been more motivated to complete the survey, as recent research has shown that males are more interested in extrinsic motivations when participating in life sciences research, whereas females also value intrinsic motivations, such as helping society [ 61 ]. Finally, our survey did not assess medical or mental health conditions or any treatments that participants were undergoing (e.g., depression and antidepressant medication), which could have impacted upon the wellbeing and WRQOL scores in our sample.…”
Section: Discussionmentioning
confidence: 99%